Mechanisms and applications of N-Methyl-N’-nitro-N-nitrosoguanidine in animal tumor models: current situation and challenges - Zhang, Xiyan; Xu, Yupei; Cao, Junwen; Li, Tong; Wang, Jiaqi; Tao, Jingna; Zhang, Liju; Li, Zhihong (Frontiers in Oncology, 2025)
The worldwide health and economic burden of cancer is substantial, necessitating urgent, focused prevention and treatment strategies. The investigation of cancer animal modeling techniques is particularly critical. N-methyl-N’-nitro-N-nitrosoguanidine (MNNG), a nitrosamine carcinogen, is extensively utilized in the development of several tumor animal models due to its ability to replicate the natural onset of cancer. Nonetheless, MNNG exhibits a propensity for multi-organ carcinogenesis; yet, this aspect remains undiscussed. The MNNG model exhibits distinct characteristics depending on the route of administration, yet it also presents inherent limitations such as toxicity, environmental contamination, and inconsistent modeling outcomes. These issues necessitate standardized protocols to refine the model, ensuring it meets the criteria for efficient and precise tumor induction while adhering to animal welfare principles. This study examines the current applications of MNNG in gastric cancer models and models of other organs, its carcinogenic mechanisms, translational relevance to human tumors, and practical application features, with a particular focus on its use in gastric contexts. Furthermore, it summarizes and compares the advantages and disadvantages of various MNNG administration routes, as well as contrasts its carcinogenic properties with those of other chemical inducers.Through the examination of drug administration routes, dosage effects, combined modeling strategies, and model specificity, we endeavored to identify effective methods to enhance the specificity of target organs by optimizing the administration approach (local exposure, integration of advanced detection technologies with auxiliary factors). Furthermore, we encourage researchers to disclose negative results, as this practice helps improve model stability and accuracy, reduces research costs, and aligns with animal welfare guidelines.Experimental animals are crucial in scientific study. Future investigations must develop standardized protocols to minimize non-target organ damage and examine the interaction mechanisms between these animals and the tumor microenvironment.